PATTERN OF NEONATAL MORBIDITY AND MORTALITY IN THE NEONATAL INTENSIVE CARE UNIT - Zaman, Saeed; Shahzad, Suhail; Shah, Sajid Ali (Pakistan Armed Forces Medical Journal, 2017)
Objective: To document the burden of different diseases, their pattern and outcome in neonates admitted to neonatal intensive care unit (NICU) of Combined Military Hospital (CMH) Malir Cantt, Karachi.Study Design: A descriptive study.Place and Duration of Study: The study was carried out in CMH Malir over a period of one year, from Jan 2011 to Dec 2011.Patients and Methods: Data of all admitted patients during the study period was reviewed and analyzed in terms of age, sex, weight, place and mode of delivery, cause of admission and their outcome. Diagnosis was made on clinical basis, radiological findings and laboratory investigations. Data were analyzed using SPSS version 18.Results: Total number of patients was 1020. Males were 556 (54.51%) and females were 464 (45.49%). The most common reason for admission was preterm/low birth weight (PT/LBW) i.e. 494 (48.43%) followed by neonatal sepsis which were 200 (19.61%), respiratory distress syndrome (RDS) 74 (7.25%), neonatal jaundice 65 (6.37%), meconium aspiration syndrome (MAS) 53 (5.20%), birth asphyxia (BAS) 51 (5%), transient tachypnea of newborn (TTN) 40 (3.92%), congenital malformations 27 (2.65%), infant of diabetic mother 9 (0.88%), neonatal seizures 6 (0.59%) and hemorrhagic disease of the newborn 1 (0.10%). The numbers of patients discharged were 947 (92.84%) and those patients who expired were 73 (7.16%). The commonest causes of death were PT/LBW 34 (46.57%) and neonatal sepsis 15 (20.55%).Conclusion: In our study the commonest causes of admission were PT/LBW and neonatal sepsis. Mortality was more for PT/LBW and neonatal sepsis both of which can be reduced by proper antenatal care, safe reduction in lower segment caesarian section (LSCS) and improvement in NICU care.